2011
DOI: 10.1080/00207144.2011.622215
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotherapy Intervention for Loin Pain Hematuria:A Case Study

Abstract: Loin pain hematuria is characterized by chronic loin pain, hematuria, and dysuria. There are no known effective treatments for loin pain hematuria and longer-term use of analgesics and surgical options are often ineffective or associated with negative side effects. This article reports on a 17-year-old female patient diagnosed with loin pain hematuria who presented with unilateral, uncontrolled loin pain following numerous unsuccessful attempts at controlling her symptoms with traditional medical interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The exact cause remains elusive but it has been suggested that the hematuria may be attributable to a thin glomerular basement membrane, which creates an occlusion within the renal tubules and thus flank pain because of capsular expansion. 9 The treatment is difficult as evidenced by the various treatments described in the literature including intraureteral capsaicin, 10 hypnotherapy, 11 and intrathecal opioids. 12 Hebert et al 13 described the use of angiotensin-converting enzyme inhibitors in the management of LPHS to decrease glomerular hemorrhage and therefore pain.…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause remains elusive but it has been suggested that the hematuria may be attributable to a thin glomerular basement membrane, which creates an occlusion within the renal tubules and thus flank pain because of capsular expansion. 9 The treatment is difficult as evidenced by the various treatments described in the literature including intraureteral capsaicin, 10 hypnotherapy, 11 and intrathecal opioids. 12 Hebert et al 13 described the use of angiotensin-converting enzyme inhibitors in the management of LPHS to decrease glomerular hemorrhage and therefore pain.…”
Section: Discussionmentioning
confidence: 99%